Blood glucose control and opportunities for clinical pharmacists in infectious diseases ward - Minoosh Shabani; Maryam Rashedi; Sareh Razzazzadeh; Ali Saffaei; Zahra Sahraei (Wolters Kluwer Medknow Publications, 2019)
Objective: Increased risk of infection following hyperglycemia has been reported in hospitalized patients. Sliding-scale insulin protocol is an out-of-date method; therefore, it is necessary to examine new approaches in this regard. This study aimed to evaluate the efficacy of sliding-scale protocol versus basal-bolus insulin protocol, which supervised by clinical pharmacists in an infectious disease ward. Methods: In this prospective randomized clinical trial, 90 hyperglycemic patients who hospitalized in Loghman Hakim Hospital Infectious Disease Ward (Tehran, Iran) were randomized into two groups: sliding-scale insulin protocol (the control group) and the basal-bolus protocol groups that were under supervision clinical pharmacists. Some demographic, laboratory, and clinical variables, as well as patient's blood glucose were measured four times daily. Findings: The results indicated significant improvement among the patients in the intervention group. General indicators including fever, blood glucose level, the duration of hospitalization, incidence of hypoglycemia, days to achieve normal blood glucose, and leukocyte count improved in intervention group. Conclusion: According to this study, basal-bolus insulin protocol, which supervised by clinical pharmacy service, showed better blood glucose control and infection remission compared to the sliding-scale protocol.